1971
DOI: 10.1017/s0007485300057771
|View full text |Cite
|
Sign up to set email alerts
|

The effects of smoke from mosquito coils on Anopheles gambiae Giles and Mansonia uniformis (Theo.) in verandah-trap huts at Magugu, Tanzania

Abstract: IntroductionSmoke from mosquito coils is widely used as a method of reducing the nuisance from mosquitoes, particularly in South-East Asia, Japan, parts of Africa and South America (Maclver, 1963). Laboratory tests showed coils containing pyrethrins to have several effects on mosquitoes. Maclver (1964a) using blood-fed Aedes aegypti (L.) caged about 8 cm from a coil in a closed room found that there was a decrease in the KD90 (time to knockdown of 90%) from 105 min with coils containing 0-1% pyrethrins to 20 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…by thermal expulsion was comparable with that of a mosquito coil that was used as a positive control in this field trial. The level of repellency of mosquito coil in this study is in agreement to reports of 24–88% reduction from Tanzania and Papua New Guinea (Hudson & Esozed 1971; Charlwood & Jolly 1984). The continuing repellency of plants after application by thermal expulsion showed that thermal fumigation in the early hours of the night may be sufficient to effectively repel mosquitoes for the remaining duration of the night.…”
Section: Discussionsupporting
confidence: 92%
“…by thermal expulsion was comparable with that of a mosquito coil that was used as a positive control in this field trial. The level of repellency of mosquito coil in this study is in agreement to reports of 24–88% reduction from Tanzania and Papua New Guinea (Hudson & Esozed 1971; Charlwood & Jolly 1984). The continuing repellency of plants after application by thermal expulsion showed that thermal fumigation in the early hours of the night may be sufficient to effectively repel mosquitoes for the remaining duration of the night.…”
Section: Discussionsupporting
confidence: 92%
“…The burning of pyrethroid coils protected individuals outdoors. Similar reductions have been reported by other workers in Africa (Hudson & Esozed, 1971;Smith et al, 1972) and in Papua New Guinea (Charlwood & Jolley, 1984).…”
supporting
confidence: 89%
“…Although the impregnated eave curtains were consistently less efficient than the nets with which they were compared, they still provided about as much protection (57-7396) in the verandah-trap huts (Table 6) as the pyrethrum mosquito coils tested in the same huts by Smith et al (1972) and Hudson & Esozed (1971). Like the nets.…”
Section: Personal Protection With Nets and Curtainsmentioning
confidence: 84%